Soviet Industrial Sociology, 1960s-1970s - Sheila Pattle (Revue d’Histoire des Sciences Humaines)
To understand the rapid development of Soviet industrial sociology in the 1960s, it is essential to look beyond the Academy of Sciences in Moscow and focus instead on very specific local environments where higher educational institutions established sociological research institutes. The institutes’ work comprised scientific research projects and numerous projects carried out under economic contracts with industrial enterprises. The latter certainly supported the rapid growth in the numbers of institutes and sociologists in the 1960s and 1970s. However, there were significant constraints in redeploying the project results for academic purposes. In addition, sociology more broadly turned towards ideological conformism from 1972. As a result, the institutes’ scientific leaders focused on constructing a consensus around the methodology of sociological research.